(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
Having an accurate picture of children’s social behavior and abilities is of central importance in education. Prerequisites for the development of social competence are high self-esteem, positive attitudes towards the environment, acceptance and effective communication. Different kinds of speech impairments, speech disorders and articulation problems arising as a result of various impairments impede interaction between the individual and the environment, hinder accommodation and social adjustment. The activity of the speech therapist is, at the same time, therapeutic and educational in nature, while it focuses on the entire personality of the student. The present study reviews special techniques and methods in speeck therapy that contribute to social competence development of pre-school stuttering children.